Notes on the genera Sinophasma Günther, 1940 and Pachyscia Redtenbacher, 1908 (Phasmatodea: Diapheromeridae: Necrosciinae), with the description of four new species from China - Ho, George Wai-Chun (Zootaxa, 2012)
A list and key to the species of Sinophasma Günther, 1940 and Pachyscia Redtenbacher, 1908 are provided. Four new species, Sinophasma bii sp. nov., S. daoyingi sp. nov., S. guangdongensis sp. nov. and Pachyscia heishidingensis sp. nov., from China are described and illustrated. One new synonym and one new combination are established: Sinophasma rosarum Chen & He, 2008 is shown to represent the female of S. jinxiuense Chen & He, 2008 (syn. nov.); and Pachyscia longicauda (Bi, 1990) (comb. nov.) is transferred from Sinophasma. The male of Pachyscia dilatata (Chen & He, 2004) is described for the first time.